ANALISIS KONSEP DASAR SISTEM INFORMASI MANAJEMEN UNTUK MENDUKUNG TRANSPARANSI DI BANK SYARI’AH INDONESIA KCP KRAKATAU - Miranti Agustina; Nurhikmah Berasa; Mella Afrina; Nurbaiti (CV. Barokah Publsiher, 2025)
This study aims to analyze the fundamental concept of Management Information Systems (MIS) in supporting transparency at Bank Syariah Indonesia (BSI) Krakatau Sub-Branch Office. Transparency is one of the main principles of sharia governance, playing a crucial role in building customer trust and enhancing the accountability of Islamic financial institutions. The research employs a descriptive qualitative method using a case study approach at BSI Krakatau Sub-Branch through interviews, observations, and documentation. The findings reveal that the application of basic MIS concepts at BSI Krakatau has contributed to improving information disclosure, accelerating service processes, and enhancing the effectiveness of internal supervision. However, further optimization is needed in data integration and the comprehensive use of digital technology. This study concludes that MIS plays a strategic role in realizing transparency and good governance in Islamic banking institutions.